(untitled) (The Review of Diabetic Studies, 2024)
Background:​‍​‌‍​‍‌​‍​‌‍​‍‌ Medically Unexplained Symptoms (MUS) are a significant source of clinical challenge, which account for 5-11% of patients in primary care and that in turn is the cause of a large part of the wastage of healthcare resources through needless investigations and referrals to specialists. Optimizing patient outcomes while cutting healthcare costs is achievable through an integrated and collaborative approach that treats medical, laboratory, and psychological aspects simultaneously. Objective: To measure the effectiveness of a collaborative multidisciplinary protocol involving Family Medicine, Laboratory Services, and Mental Health in managing MUS patients. The study also aimed to observe changes in resource utilization and clinical outcomes. Methods: This mixed-methods study presents 18-month data on 485 patients with diagnostically confirmed MUS who were managed under the new collaborative protocol. These patients were compared with 520 historical controls who received standard care. The main outcomes were healthcare resource utilization, symptom severity, quality of life, and patient satisfaction. Secondary outcomes examined cost-effectiveness and the clinical course of MUS. Results: The collaborative protocol brought about major reductions in unnecessary investigations (47% reduction, p<0.001), specialist referrals (39% reduction, p<0.001), and emergency department visits (52% reduction, p<0.001). On average, the healthcare costs were reduced by €2,847 per patient per year (p<0.001). The patient satisfaction rate went up from 52% to 89% (p<0.001), and symptom severity was considerably improved as well (baseline M=7.2 to M=4.1 at 18 months, p<0.001). The proportion of patients whose symptoms went into remission was 42% as compared to only 18% of the control group ​‍​‌‍​‍‌​‍​‌‍​‍‌(p<0.001). Conclusions: The collaborative protocol led to a significant improvement in clinical outcomes, increase in patient satisfaction, and a substantial decrease in healthcare resource wastage in patients with MUS. This is a cost-effective approach to managing a common and resource-intensive condition. It is recommended that collaborative protocols be widely implemented as a priority for the optimization of the healthcare system.